2016
DOI: 10.3390/metabo6040032
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Extending Metabolomics Studies with Stable Isotope Labelling and Fluxomics

Abstract: This is a perspective from the peer session on stable isotope labelling and fluxomics at the Australian & New Zealand Metabolomics Conference (ANZMET) held from 30 March to 1 April 2016 at La Trobe University, Melbourne, Australia. This report summarizes the key points raised in the peer session which focused on the advantages of using stable isotopes in modern metabolomics and the challenges in conducting flux analyses. The session highlighted the utility of stable isotope labelling in generating reference st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 96 publications
(124 reference statements)
0
25
0
Order By: Relevance
“…An alternative approach is to use selected reaction monitoring (SRM) methods, whereby the mass spectrometer is set to only select and record specific precursor/product ion combinations from the unfractionated complex mixture, greatly increasing detection sensitivity as the majority of a sample can then be rejected and ignored. The use of stable isotope‐labeled (commonly deuterium, 15 N or 13 C) metabolites can also be highly informative in focused analyses, as they allow the analyst to follow metabolic flux from a given metabolite and verify changes detected in global analyses.…”
Section: Indirect/phenotype‐based Methodsmentioning
confidence: 99%
“…An alternative approach is to use selected reaction monitoring (SRM) methods, whereby the mass spectrometer is set to only select and record specific precursor/product ion combinations from the unfractionated complex mixture, greatly increasing detection sensitivity as the majority of a sample can then be rejected and ignored. The use of stable isotope‐labeled (commonly deuterium, 15 N or 13 C) metabolites can also be highly informative in focused analyses, as they allow the analyst to follow metabolic flux from a given metabolite and verify changes detected in global analyses.…”
Section: Indirect/phenotype‐based Methodsmentioning
confidence: 99%
“…When used in the context of biomarker discovery and verification, stable isotope labeling can be used to quantify the biomarkers of interest and provide mechanistic insight into the biochemistry of the cancer cells. This approach usually works by utilizing nutrients enriched with stable isotopes of atoms that occur naturally in biomolecules (such as 2 H, 13 C, 15 N, and 34 S) and performing labeling experiments over a time course to observe the dynamic nature of metabolism . Using this approach, it has been shown that compared to normal cells, cancer cells express a different isoform of the glycolytic enzyme pyruvate kinase (M2), which is associated with the accumulation of phosphoenolpyruvate, 3‐phosphoglycerate, and serine .…”
Section: Metabolomics Approaches For Biomarker Discoverymentioning
confidence: 99%
“…Quantitation of metabolic fluxes through each reaction within a network can only be estimated indirectly with the help of isotopically labeled metabolic tracers (Gaudin et al 2014;Gleixner et al 1998;Sauer 2006). Fluxomics studies such as stable isotoperesolved metabolomics (SIRM) are emerging as powerful strategies used to measure fluxes in complex interconnected metabolic networks (Kikuchi et al 2004;Maroli et al 2016;Srivastava et al 2016). In weed science, only a couple of studies have used fluxbased omics studies to examine competitive physiology (Maroli et al 2016;Miyagi et al 2011).…”
Section: Metabolomics and Fluxomics To Understand Weed Physiologymentioning
confidence: 99%